The Expression of the fim Operon Is Crucial for the Survival of Streptococcus parasanguinis FW213 within Macrophages but Not Acid Tolerance. - Yi-Ywan M Chen (PLoS ONE, 2013)
The acquisition of transition metal ions is essential for the viability and in some cases the expression of virulence genes in bacteria. The fimCBA operon of Streptococcus parasanguinis FW213 encodes a Mn(2+)/Fe(2+)-specific ATP-binding cassette transporter. FimA, a lipoprotein in the system, is essential for the development of endocarditis, presumably by binding to fibrin monolayers on the damaged heart tissue. Recent sequence analysis revealed that Spaf_0344 was homologous to Streptococcus gordonii scaR, encoding a metalloregulatory protein for the Sca Mn(2+)-specific transporter. Based on the homology, Spaf_0344 was designated fimR. By using various fim promoter (p fim ) derivatives fused with a promoterless chloramphenicol acetyltransferase gene, the functions of the cis-elements of p fim were analyzed in the wild-type and fimR-deficient hosts. The result indicated that FimR represses the expression of p fim and the palindromic sequences 5' to fimC are involved in repression of p fim . A direct interaction between FimR and the palindromic sequences was further confirmed by in vitro electrophoresis gel mobility shift assay and in vivo chromatin immunoprecipitation assay (ChIP)-quantitative real-time PCR (qPCR). The result of the ChIP-qPCR analysis also indicated that FimR is activated by Mn(2+) and, to a lesser degree, Fe(2+). Functional analysis indicated that the expression of FimA in S. parasanguinis was critical for wild-type levels of survival against oxidative stress and within phagocytes, but not for acid tolerance. Taken together, in addition to acting as an adhesin (FimA), the expression of the fim operon is critical for the pathogenic capacity of S. parasanguinis.